Studies on influence of rapeseed vegetation stages on level of phenolic compounds (Journal of Oilseed Brassica, 2026)
A study was conducted to evaluate the changes in native antioxidants in rapeseed (Brassica napus L), which take place during crop growth. During the growth, in anatomical parts of plants (Kana and Spencer varieties), the increased content of hydrophilic antioxidants (phenolic compounds) was observed. During the plant maturation the decrease of phenolic acids was observed both in leaves during blooming and in hulls. During that time, total phenolic acid content decreased by 50% in Kana and by 40% in Spencer. The profile of phenolic acids in sampled rapeseed varieties was characterized by the highest level of sinapic acid and its low molecular derivative. It was proved, that during successive stages of maturation, the content of phenolic acids varied in anatomical parts of the plant. This may suggest different biological functions of particular phenolic compounds.